Examining Prospective Teachers’ Metacognitive Learning Strategies and Self-Regulated Online Learning Levels During Covid-19 Pandemic - Akyıldız, Seçil Tümen; Kaya, Vildan Donmuş (Muhammed ZİNCİRLİ, 2021)
By Covid-19 pandemic online or distance learning came to foreground to resolve the educational crisis. Student-centred practices were recommended by educators to weather the storm. That’s why including self-regulated learning (SRL) and metacognitive learning strategies (MLS) to the online learning are considered necessary. Thus, this study aimed at investigating the use of self-regulated online learning (SROL) and MLS levels of students, the relationship between them, how the use of MLS predicts Turkish prospective teachers’ online SRL capacity through the time of emergency remote education, and contributing to the new educational paradigm after the pandemic. The study was designed as a correlational survey model including 567 prospective teachers at Fırat University Faculty of Education in Turkey. The data were collected by MLS determining scale and SROL questionnaire for prospective teachers. The data were analyzed by t-test, ANOVA and simple linear regression. The results revealed that the participants have high levels of SROL and use MLS frequently. While SROL and MLS levels of participants do not differ in terms of gender; they differ with regard to participants’ departments, class levels and time of self-study. Lastly the use of MLS was a positive predictor of SROL.